If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(-1m + 4m) = -6 Combine like terms: -1m + 4m = 3m -1(3m) = -6 Remove parenthesis around (3m) -1 * 3m = -6 Multiply -1 * 3 -3m = -6 Solving -3m = -6 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Divide each side by '-3'. m = 2 Simplifying m = 2
| 2n^2-9n+2=-2 | | 2n^2-9n+2=2 | | x+1=3k-1 | | 2x+1y=3.00 | | 2n^2-9n+2=0 | | 0=3/4x-3 | | 2.88x=9.12 | | 57w=450x | | 9x+3+2x=36 | | K/13=-28 | | 2+3x=-8+5 | | 12-2.88= | | 2x-14=62 | | 7-^3/2 | | fy+3=gx+-15 | | 10x^3+6x^2=0 | | -9x-40= | | 3x-2/3(2x-1)=4 | | 6+3n= | | 36x^4-81x^7=0 | | -6x-4(7x+13)=186 | | 20/6x-7/6=9/6 | | 0.18=x^12 | | 4=15r-7 | | 6(x-3)=-2(x-7) | | 6x+18=10x-6 | | 47=5x-(7-4x) | | 7x+3y=50000 | | -(3x+5)=2x | | -d+4e=-3 | | -6(x-6)=3(0+x) | | 0.5=0.4 |